The Influence of Discovery Learning on Serotonin Hormones and Student Learning Achievements - Husniyatus Salamah Zainiyati; Evi Fatimatur Rusydiyah; Hanik Faizah; Hernik Farisia; Risa Purnamasari; Qurrotul Ayun (Journal of Innovation in Educational and Cultural Research, 2023)
Discovery learning is a model designed to tackle the issue of low learning achievement. However, typically, research on discovery learning mainly focuses on outcomes to enhance specific abilities partially. Yet, discovery learning is also associated with physiological aspects. This study aims to determine the discovery of learning influence on learning achievement and serotonin. This is an experimental study. The independent variable (x) is discovery learning, whereas the dependent variables (y) are student achievement and serotonin. The statistical test used the paired sample t-test. Other data related to students' learning skills in the classroom using discovery learning were observed and analyzed with the descriptive qualitative method. There were significant differences in learning achievement and serotonin levels before and after the implementation of discovery learning.The average scores before and after the implementation of discovery learning were 46.75 and 78.55, respectively. The average hormone levels before and after the implementation of discovery learning were 719.25 and 1420.59 ng/mL, respectively. The implementation of discovery learning increases serotonin levels, thus optimizing student learning achievement. Following this research finding, research on how to increase serotonin levels through other learning methods needs to be conducted to explore many best practices that affect students' achievement.